PEMBINAAN PRESTASI CABANG OLAHRAGA TARUNG DERAJAT DI SATLAT GOR SATRIA KABUPATEN BANYUMAS TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
From the research, the results showed that the implementation of the coaching is done on pemassalan coaching experience problems due to sports Tarung Derajat can not be socialized. Facilities and infrastructure owned by the club is not entirely adequate, and additional facilities and infrastructure necessary to support the exercise. The proceeds of the club is the Sports Committee, donors, administrators, and athletes. Conducted training programs already running smoothly, the coach has given a program of physical exercise, technique, mental, and tactics. The coach who handles the coaching process in Satlat GOR Satria amounted to only one person. In the process of selecting athletes to represent the area of selection must be made not just recruit great athletes from other regions. Achievement owned Satlat GOR Satria Banyumas is in Porprov in 2013, dulongmas, Kejurkab and Kejurda.